Thanks for taking time to assist me with simplifying the following:
As you can see, I really have no idea with algebra. Thanks heaps.
- (5h -2m)^2
- x/y divide 3x/h
- 1/3xy * y * 6x
- 6mx^2 divide 2mx
- 18a(2b-c) divide 6(2b -c)
Hello,
Use the identity : $\displaystyle (a-b)^2=a^2-2ab+b^2$
$\displaystyle \frac{\frac{3x}{h}}{\frac xy}=\frac y{\color{red}x} \cdot \frac{3{\color{red}x}}{h}=\dots$x/y divide 3x/h
I guess it is :1/3xy * y * 6x
$\displaystyle \frac{1}{3xy} \cdot y \cdot 6x=\frac{2 \cdot {\color{magenta}3} \cdot {\color{blue}x} \cdot {\color{red}y}}{{\color{magenta}3} \cdot {\color{blue}x} \cdot {\color{red}y}}=\dots$
Always try to see what can simplify above and below, and it should be ok !